PENGEMBANGAN DESAIN “DIGI-MOTIF” UNTUK AKTUALISASI IDENTITAS JEPARA SEBAGAI KOTA UKIR - Agus Setyawan; Annas Marzuki Sulaiman (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
World Carving Centre is an expression that most appropriate for Jepara. Jepara hava a big potential in Handcraft can be seen in a leadership Queen Kalinyamat and R.A Kartini. A crafting design motive this moment have changed, there can take off from the role community. Who Design development motive carving who stay until now by the artist.Motive carving Jepara capable of being viewed as social construction into the room in conjunction with its cultural identity and tradition. Motive carving in made the identity of through a creation digi-motive to strenghthent the role of trhough the to strength image Jepara as world carving center. Strategy research with the qualitative approach historical and aesthetic, the data used originates from speakers, action, archives, and written source.As for technique data collection by interviews, observation, documentation and literature study and analyzed in cycle to expalain digi-motive design development and identity Jepara as City Carving. The existence of motive carving into the breath for community Jepara, so that development digi-motive sthrengthen design imagery through some form of creation digi-motive logo Jepara of them, KPU logo Jepara election , flags and mascot.Technological development created privacy. So the art of technology and people can synergi